2018
DOI: 10.1038/s41419-018-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methyltransferase SMYD2 promotes triple negative breast cancer progression

Abstract: We identified SMYD2, a SMYD (SET and MYND domain) family protein with lysine methyltransferase activity, as a novel breast cancer oncogene. SMYD2 was expressed at significantly higher levels in breast cancer cell lines and in breast tumor tissues. Silencing of SMYD2 by RNAi in triple-negative breast cancer (TNBC) cell lines or inhibition of SMYD2 with its specific inhibitor, AZ505, significantly reduced tumor growth in vivo. SMYD2 executes this activity via methylation and activation of its novel non-histone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 51 publications
4
88
1
Order By: Relevance
“…SMYD2, which belongs to the group of transcriptional regulators containing SET and MYND domains, is responsible for complex transcriptional regulation through histone methylation and non-histone protein methylation (24,25). Previous studies have suggested that SMYD2 is upregulated in several types of cancer, including pediatric acute lymphoblastic leukemia, gastric cancer and breast cancer (26)(27)(28). Additionally, previous studies have highlighted the role of SMYD2 in the regulation of cancer cell growth (13,17).…”
Section: Discussionmentioning
confidence: 99%
“…SMYD2, which belongs to the group of transcriptional regulators containing SET and MYND domains, is responsible for complex transcriptional regulation through histone methylation and non-histone protein methylation (24,25). Previous studies have suggested that SMYD2 is upregulated in several types of cancer, including pediatric acute lymphoblastic leukemia, gastric cancer and breast cancer (26)(27)(28). Additionally, previous studies have highlighted the role of SMYD2 in the regulation of cancer cell growth (13,17).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al have found that histone deacetylase 6 (HDAC6), a class II histone deacetylase, and prostaglandin E2 and COX2, can upregulate STAT3 activation in breast cancer [18]. In addition, lysine methyltransferase SMYD2 can activate the methylation and phosphorylation of STAT3 to promote breast cancer progression [19]. MicroRNA (miR) has become a hot topic in the fields of cancer biology and development in recent years.…”
Section: Advances In the Study Of Stat3 Signaling Pathways In Breast mentioning
confidence: 99%
“…The cells were scraped using sterilized 10 μL pipette tips and washed with 0.1% serum media and stimulated with PDGF‐BB (20 ng·mL −1 ) (Du et al, ). For the signalling pathway study, the following chemical inhibitors were used: S3I‐201 (100 μM) (Li et al, ), U0126 (1 μM) (Pathria et al, ), LY294002 (30 μM) (Liao et al, ), staurosporine (50 nM) (Prins et al, ) and 3‐TYP (20 nM) (Shumin et al, ). All these inhibitors were purchased from Selleck Chemicals (Houston, TX, USA).…”
Section: Methodsmentioning
confidence: 99%